The Effect of Persuasive Communication Principles On The Ability Of Vision Agent at PT Allianz Wisma GKBI Jakarta - Agustin, Priskila Nia; Poernomo, Marlinda Irwanti (International Journal Of Humanities Education and Social Sciences (IJHESS), 2023)
This research aims to see the influence of persuasive communication principles on agent vision capabilities at PT Allianz Wisma GKBI Jakarta. The research that will be studied uses a post-positivism paradigm, with a qualitative approach and descriptive methods. This research will use quantitative and qualitative research (mix method). In this research, the secondary data used was obtained from the Allianz Star Network (ASN) portal data, the Allianz Website, the Mitranewvision Website. The subjects in this research were divided into respondents and key informants. Respondents consisted of prospective customers who were offered Allianz products/potential customers who had the criteria to be offered Allianz products. This research was conducted at the Wisma GKBI Agency Vision Office, 1st floor, located at Jl Jendral Sudirman Kav 28, South Jakarta. The object of research in this study is the influence of persuasive communication principles on the abilities of Vision PT customer agents. Allianz Indonesia Wisma GKBI Jakarta. 1. The results of this research show a positive influence between the persuasive communication principles of the Selective Exposure (X1) dimension on PT's Vision Agent Ability. Allianz Indonesia in the AISAS(Y) Marketing model. 2. There is a positive influence between the persuasive communication principles of the Selective Exposure (X2) dimension on PT's Vision Agent Ability. Allianz Indonesia in the AISAS(Y) Marketing model. 3. There is no influence between the persuasive communication principles of the Inoculation dimension (X3) on PT's Vision Agent Ability. Allianz Indonesia in the AISAS(Y) Marketing model. 4. The novelty of this research is that there is a positive influence between the principles of persuasive communication in the Change dimension (X4) on PT's Vision Agent Ability. Allianz Indonesia in the AISAS(Y) Marketing model.